2006
DOI: 10.1007/s00415-006-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalization of tactile stimulation in patients with complex regional pain syndrome

Abstract: Complex-Regional-Pain-Syndromes (CRPS) are characterized by sensory,motor and autonomic dysfunctions. Patterns of sensory symptoms suggest changes within the central nervous system (CNS). Recently, we could show substantial reorganization of somatotopic maps within the central nervous system of patients with CRPS using functional imaging techniques (Maihofner et al. Neurology, 2003). These changes were predicted by CRPS pain and mechanical hyperalgesia. In the present study we looked for potential psychophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
4
47
0
2
Order By: Relevance
“…In addition to facilitated neurogenic inflammation and pathological sympatho-afferent coupling, there is accumulating evidence that central nervous system changes may be involved in the pathogenesis of CRPS [79]. Regarding the somatosensory system, there is evidence for a substantial reorganization of the somatotopic map within the primary somatosensory cortex of CRPS patients [79][80][81][82][83][84]. Using functional imaging techniques, a significant shrinkage of the cortical hand representation contralateral to the CRPS affected painful arm was found [79,81,83].…”
Section: Functional Imaging Of Neuropathic Painmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to facilitated neurogenic inflammation and pathological sympatho-afferent coupling, there is accumulating evidence that central nervous system changes may be involved in the pathogenesis of CRPS [79]. Regarding the somatosensory system, there is evidence for a substantial reorganization of the somatotopic map within the primary somatosensory cortex of CRPS patients [79][80][81][82][83][84]. Using functional imaging techniques, a significant shrinkage of the cortical hand representation contralateral to the CRPS affected painful arm was found [79,81,83].…”
Section: Functional Imaging Of Neuropathic Painmentioning
confidence: 95%
“…Cortical reorganization may be able to explain some of the often puzzling clinical signs of CRPS, e.g. the spatial distribution of sensory disturbances in a glove or stocking like distribution, the occurrence of tactile induced referred sensations [82] and hemisensory deficits. Furthermore, there is accumulating evidence that the central motor system shows significant alterations in CRPS.…”
Section: Functional Imaging Of Neuropathic Painmentioning
confidence: 99%
“…Additionally, trophic alterations in skin, hair, nails, and motor function may also occur. Experimental studies have repeatedly documented that patients with CRPS exhibit profound alterations in brain function (Fukumoto et al 1999;Apkarian et al 2001;Maihöfner et al 2004Maihöfner et al , 2005Maihöfner et al , 2006Pleger et al 2006;Lebel et al 2008;Becerra et al 2009;Freund et al 2010), structure (Geha et al 2008;Baliki et al 2011), andchemistry (Fukumoto et al 1999;Grachev et al 2000Grachev et al , 2002Klega et al 2010). Interestingly, there is growing evidence that chronic pain is also characterized by alterations in resting-state functional connectivity (rsFC) as, for example, patients with chronic pain conditions exhibit altered default mode network and attention network rsFC (Baliki et al 2008;Cauda et al 2009bCauda et al , 2010, as well as greater rsFC between pain-related brain regions compared with healthy controls (Cauda et al 2009a).…”
mentioning
confidence: 99%
“…Most previous studies on other chronic pain conditions have also demonstrated reduced gray matter in regions that are likely involved in pain modulation and limbic function (13)(14)(15)(16)(17)(18)(19). Moreover, imaging studies have linked specific aspects of neuropathic pain, such as allodynia (20), hyperalgesia (21), mislocation (22), and shooting pain (23), with particular brain structures and networks.…”
mentioning
confidence: 99%